Weighted singular decomposition and weighted pseudoinversion of matrices - Galba, E. F.; Галба, Е. Ф.; Галба, Е. Ф. (Institute of Mathematics, NAS of Ukraine, 1996)
For a rectangular real matrix, we obtain a decomposition in weighted singular numbers. On this basis, we obtain a representation of a weighted pseudoinverse matrix in terms of weighted orthogonal matrices and weighted singular numbers.